Behavior-modified T-stub steel connection against cyclic loads - Prasetyo, Totok Andi; Antonius, Antonius; Sumirin, Sumirin (International Journal of Innovative Research and Scientific Studies, 2025)
This study investigates the structural behavior of a Modified T-Stub steel connection under cyclic loading through both numerical simulations and experimental testing. The primary objective is to evaluate whether the Modified T-Stub connection meets the criteria for Special Moment Frame (SMF) Prequalification, as outlined in SNI 7972:2020. Two test specimens were analyzed: Specimen 1 (WF 450x200x9x14) and Specimen 2 (WF 500x200x10x16), each paired with a WF 588x300x12x20 column. Numerical simulations were conducted using IDEA StatiCa and ANSYS software, while experimental testing was performed at the PUPR Laboratory. In the laboratory, an actuator was used to push the column with a 100-ton capacity, and we installed 21 strain gauges and 19 transducers to check deformation and strain in the members. The numerical analysis revealed that Specimens 1 and 2 reached drift ratios of 5% and 4%, respectively, meeting the required seismic performance standards. Experimental results confirmed similar findings, with drift ratios of 4% and 5%, and plastic moments exceeding 502 kN·m for Specimen 1 and 603 kN·m for Specimen 2. The yield load for Specimen 1 is 179 kN, and the yield load for Specimen 2 is 224 kN. Tension and compression at the flange for Specimen 1 are 1644 kN, while compression and tension at the flange for Specimen 2 are 1816 kN. Both approaches showed that plastic deformation occurred in the beam segment beyond the connection, indicating effective energy dissipation. These findings validate the Modified T-Stub as a viable alternative for prequalified moment-resisting connections in seismic steel structures. The practical implication is a simplified installation process for steel beams that enhances construction efficiency in terms of time and cost while maintaining seismic safety compliance. The rotation for Specimen 1 and Specimen 2 are 5% and 4%, respectively, which meets the AISC regulation if the connection is a Special Moment Frame Prequalification.